IFMIF, the European–Japanese efforts under the Broader Approach agreement towards a Li(d, xn) neutron source: Current status and future options. (December 2016) - Knaster, J.; Arbeiter, F.; Cara, P.; Chel, S.; Facco, A.; Heidinger, R.; Ibarra, A.; Kasugai, A.; Kondo, H.; Micciche, G.; Ochiai, K.; O'hira, S.; et al.
Highlights: Description of the technical achievements of IFMIF in its final EVEDA phase. Explanation of technical difficulties overcome of the main historical technical challenges for a Li(d, xn) fusion relevant neutron source. Abstract: The necessity of a neutron source for fusion materials research was identified already in the 70s. Though neutrons induced degradation present similarities on a mechanistic approach, thresholds energies for crucial transmutations are typically above fission neutrons spectrum. The generation of He via 56 Fe (n, α) 53 Cr in future fusion reactors with around 12 appm/dpa will lead to swelling and structural materials embrittlement. Existing neutron sources, namely fission reactors or spallation sources lead to different degradation, attempts for extrapolation are unsuccessful given the absence of experimental observations in the operational ranges of a fusion reactor. Neutrons with a broad peak at 14 MeV can be generated with Li(d, xn) reactions; the technological efforts that started with FMIT in the early 80s have finally matured with the success of IFMIF/EVEDA under the Broader Approach Agreement. The status today of five technological challenges, perceived in the past as most critical, are addressed. These are: 1. the feasibility of IFMIF accelerators, 2. the long term stability of lithium flow at IFMIF nominal conditions, 3. the potential instabilities in the lithium screen induced by the 2 × 5 MW impacting deuteron beam, 4. the uniformity of temperature in the specimens during irradiation, and 5. the validity of data provided with small specimens. Other ideas for fusion material testing have been considered, but they possibly are either not technologically feasible if fixed targets are considered or would require the results of a Li(d, xn) facility to be reliably designed. In addition, today we know beyond reasonable doubt that the cost of IFMIF, consistently estimated throughout decades, is marginal compared with the cost of a fusion reactor. The less ambitious DEMO reactor performance being considered correlates with a lower need of fusion neutrons flux; thus IFMIF with its two accelerators is possibly not needed since with only one accelerator as the European DONES or the Japanese A-FNS propose, the present needs > 10 dpa/fpy would be fulfilled. World fusion roadmaps stipulate a fusion relevant neutron source by the middle of next decade, the success of IFMIF/EVEDA phase is materializing this four decades old dream.